Abundance, Biomass and Alginate Yield of Padina australis in Sumbawa Aquatic - Neri Kautsari; Yudi Ahdiansyah (Jurnal Perikanan dan Kelautan, 2016)
Padina australis is one of brown seaweed which mostly found in Sumbawa coastalarea. This seaweed has a potential as a raw material for alginate. We examinedabundance, biomass and alginate content of P. australis. Data were collectedmonthly from October 2012 to January 2013. Sampling was located in the aquaticof Sumbawa Regency by the number of stations is 3 stations. Station 1 was locatedin the aquatic of Labuhan Badas District, stations 2 and 3 were in the aquatic ofBungin Island. The highest value of biomass were found on May in station 1(33.98 g wet weight/m2) and the lowest values on station2 (3.12 g wet weight/m2).Alginate content showed the highest value of 6.65% on May in station 1 and thelowest value of 3.08% on July in station 2. The results showed that biomass andalginate contents of P. australis significantly influenced by interaction of physicaland chemical enviromental factors. P. australis grew in station 1 on May had thehighest biomass and alginate contents with characteristics of physical andchemical enviromental were hard substrate, current 0.40 m s-1, pH 8, temperature32°C and salinity 32 psu.